The novobiocin-induced turnover of fibronectin via low density lipoprotein receptor-related protein 1 alters matrix morphology with physiological consequences on cell growth and migration - Boёl, Natasha Marie-Eraine (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2020)
Fibronectin (FN), an extracellular matrix protein, is secreted as a soluble dimer which is assembled into an insoluble extracellular matrix. The dynamics of FN matrix assembly and degradation play a large role in cell migration and invasion thereby contributing to the metastatic potential of cancer cells. Previous studies have shown the direct binding of Heat Shock Protein 90 kDa (Hsp90) and FN in vitro, and that inhibition of Hsp90 with novobiocin (NOV) caused internalisation of the FN matrix. Low density lipoprotein receptor-related protein 1 (LRP1) is a ubiquitous receptor known to bind both Hsp90 and FN. Using an LRP1 expressing Hs578T breast cancer cell line and an isogenic mouse embryonic fibroblast (MEF) model system of differential LRP1 expression we demonstrate that LRP1 is involved in turnover of FN in response to C-terminal Hsp90 inhibition. The first objective of this study was to identify the mechanism of NOV-induced LRP1-mediated FN turnover. Our data show that NOV-mediated FN turnover via LRP1 did not require the activity of matrix metalloproteinases (MMPs), which play an important role in processing and degradation of the extracellular matrix and FN. In addition, the levels of the main FN receptor responsible for its extracellular assembly, Î²1-integrin, did not change in response to NOV. LRP1 is known to undergo regulated intramembrane proteolysis (RIP) which generates smaller fragments that may translocate to the nucleus and modulate gene transcription. Using inhibitors of LRP1 cleavage and nuclear fractionation we determined that LRP1 processing was not required for the NOV-induced FN response suggesting that a mechanism unrelated to LRP1 RIP is involved. A possible mechanism may be in altered Hsp90-LRP1 cell signalling as we observed disruption of the FN-Hsp90-LRP1 complex at the cell surface in NOV treated cells. How this affects downstream eHsp90-LRP1 signalling is still to be determined but may be related to a significant increase in phospho-AKT and loss of phospho-ERK upon NOV-treatment; two key signalling proteins involved in FN matrix regulation and which are downstream of LRP1 signalling. The second objective of this study was to determine the physiological consequences associated with FN turnover in response to NOV treatment. Using migration assays we demonstrated that levels of insoluble matrix-associated FN and FN concentration are not solely responsible for migratory capacity of cells on decellularized extracellular matrices, but rather that structural composition and integrity of the matrix plays a bigger role. Using confocal and scanning electron microscopy, we identified NOV treated matrices to be flatter, less mature and contain thicker, rope-like FN fibrils to which cells adhered better but were generally less proliferative. Comparatively, cells adhered less to the more mature and 3-dimensional untreated matrices but exhibited increased spreading and cell growth, which may in part be due to the thinner fibrils and web-like matrix. In summary, this study substantiates the role of LRP1 in NOV-mediated FN turnover, and provides new insights into the possible mechanisms of the Hsp90-LRP1 mediated loss of FN matrix. This is the first study to demonstrate some of the functional consequences related to FN turnover by NOV at the ECM level.
Keywords: Novobiocin; Fibronectin matrix formation; Lipoproteins; Cells Growth